Perilaku Kerja Aparatur Pemerintah Daerah di Unit Satuan Polisi Pamong Praja Kota Manado - Pandi, Angellien J. S; Lumolos, Johny (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract: The purpose of the research was to find out and examine the behavior of Satpol PP members as local government officials in Manado City in carrying out duties and functions. The research method used was qualitative research by collecting data through interviews, observation and documentation. Informants were drawn from the civil service in Satpol PP amounted to 7 persons, 2 persons of voluntary members and 1 persons of temporary members, plus the 5 persons from the community so that the overall total of 15 informants. The results showed Satpol PP in performing tasks were shown to perform less disciplined behavior, especially in terms of presence that only followed the morning and evening briefings, especially for civil service personnel. Their motivation to work just to earn salary and earnings for staff and for the volunteers member, their motivation were solel a full time civil servant. Many of the personnel who had not mastered basic tasks and functions as well as the law managed to be hired without going through the selection process so that in performing their duties in the field are performing arrogant, emotional tendencies and even accepted bribes. With their average education of high school level and less training opportunities led to the lacking of knowledge and skills for the specific field task assigned to them. Based on the results of research, it could be concluded that the behavior of personnel working  in the Manado City Civil Service Police Unit has not demonstrated consistent behavior with the provisions regarding the duties and functions and community expectations on the behavior of the police civil service as a protector  and social security guards. Attitudes and behavior that did not comply with standard of performance and expectations of society that came from competence  and personal integrity officers and the influences of the environment in which they served.  Less conducive working atmosphere, as well as monitoring and enforcement of discriminatory discipline was less consistent and not sustainable, influenced attitudes and behavior of personnel in the work. In order to establish a good behavior, the knowledge, attitude and discipline have an important role in shaping the behavior of personnel in the agency. Key Words:  work behavior,motivation and  performing tasks Satpol PP